Data linkage of Psychiatric and Maternity data to investigate the pregnancy outcomes of women with Non-affective Psychosis in Scotland. (2017) - Mcskimming, Paula; Barry, Sarah; Park, John; Bhattacharya, Sohinee; MacBeth, Angus
No abstract available